Fabrication and Magnetic Properties of Sintered SrFe\(_12\)O\(_19\)-NiFe\(_2\)O\(_4\) Nanocomposites - Nga, Tran Thi Viet; Loan, To Thanh (Communications in Physics, 2017)
Two series of SrFe\(_12\)O\(_19\)/NiFe\(_2\)O\(_4\) nanocomposite ferrites sintered in air at 850C and 950C were prepared using SrFe_12O_19 and NiFe\(_2\)O\(_4\) nanopowders obtained via sol-gel method. The phase composition, surface morphology and magnetic properties of the composites were investigated using XRD, SEM and VSM respectively. For the SrFe_12O_19/NiFe_2O_4 ferrites with volume ratio ranging from 61 to 21 and sintered in 850\(\)C for 5 hours in air, all the specimens are composed of two phases but exhibit a typical single-phase magnetic behavior, indicating the existence of exchange coupling (EC) between the magnetically hard and soft phases. The value of coercivity H\(_c\) decreases from 6.19 kOe to 0.574 kOe when volume of SrFe_12O_19 decreases from 6 to 1. While the samples with a mass ratio of \(R_m\)= SrFe\(_12\)O\(_19\)/ NiFe\(_2\)O\(_4\) varying from 31 to 13 sintered in 950C for 5 hours characterized with a ``bee waist’’ type hysteresis loop. These results reveal that the magnetically hard and soft magnetic phases are not exchange- coupled. The saturation magnetization (\(M_S\)) increases from 36 emu/g to 43.3 emu/g when \(R_m\) decreases from 31 to 13 and then decreases with \(R_m= 12\) and 13.